Entre despachos fiscales y trámites : un estudio descriptivo y correlacional sobre la penalización del aborto por violación sexual - Aguilar Santa Cruz, Lisbeth Celinda (Colección derecho, 2023)
This book is based on a research whose objective is to establish the relationship between the criminalization of abortion and rape. A descriptive, propositional and correlational design was used, and 30 criminal lawyers and prosecutors in the city of Rioja were surveyed. The results show that the level of knowledge of the criminalization of abortion and double violence against women was high in 63.3% of the respondents, while the level of sexual violence in cases processed in prosecutors' offices in the province of Rioja was high in 53.3%. It was concluded that there is a strong relationship between the criminalization of abortion and rape, and that the legal model of criminalization of abortion for rape that contributes to the termination of pregnancy does not constitute double violence against women.